Faktor Yang Mempengaruhi Financial Perfomance Pada Perusahaan Bumn Yang Terdaftar Di BEI - Dwiki Gunawan, Herlin Tundjung (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study was to analyze the effect of independent variables of working capital, capital structure, and sales growth on financial performance. This study uses company size as control variable. The sample in this study was selected using purposive sampling method so that as many as 20 companies from 25 BUMN companies listed on the IDX were used as research objects. This study uses secondary data which is processed using panel data regression analysis and application Eviews version 11. Based on the analysis, it is found that working capital, capital structure, sales growth, and company size simultaneously have a significant effect on financial performance. The results of this study indicate that working capital and capital structure have a positive and significant effect on financial performance, sales growth has a positive and insignificant effect on financial performance, and company size has a negative and significant effect on financial performance. The implication in this research is the need to increase the role of the company in providing good signals to investors, especially in the form of sales growth results that will improve financial performance.